The Commonwealth guide to advancing development through sport - Kay, Tess (Commonwealth Secretariat LondonGB)
Aims to provide support for Commonwealth governments and other key stakeholders seeking to strengthen the contribution of sport to development and peace work. Recognises that the use of sport for development and peace-building has increased rapidly in the last two decades as the broad Sport for Development and Peace (SDP) movement has gained increased profile and credibility.